Effect of two semen collection in a breeding season on the seminal quality of red-bellied pacu (Piaractus brachypomus) - Suárez-Martínez, Roger Oswaldo (2019)
The effect of two semen collections performed in the same breeding season on the sperm parameters and physicochemical composition of the seminal plasma of Piaractus brachypomus was evaluated. The semen of nine hormone-induced males with hypophysial carp extract (HCE) was collected in April and May 2014. Changes between semen collections in seminal volume (SV), sperm motility (SM), motility duration (MD), sperm concentration (SC) and biochemical composition (Na+, Ca2+, Mg2+, Cl-, K+, glucose, triglycerides, protein, osmolarity and pH) were evaluated. Significant differences were observed between collections for Na+, triglycerides and osmolarity (p<0.05) and Ca2+ (p<0.01). On the other hand, no significant differences were found in SV, SM, MD and SC between collections. The collection of semen from a hormonally induced male in two occasions in one reproductive season is a viable alternative for P. brachypomus, although plasma components may vary due to sampling.